ANTI-QUORUM SENSING ACTIVITY OF SOME MEDICINAL PLANTS - Al-Haidari, Rwaida A.; Shaaban, Mona I.; Ibrahim, Sabrin R.M.; Mohamed, Gamal A. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Quorum sensing is the key regulator of virulence factors of Pseudomonas aeruginosa such as biofilm formation, motility, productions of proteases, hemolysin, pyocyanin, and toxins. Material and Methods: Quorum sensing inhibitory (OSI) effect of the alcohol extracts of 20 medicinal plants was evaluated by Chromobacterium violaceum reporter using agar cup diffusion method. The efficient QSI extracts were tested for their activity against biofilm synthesis, motility, and synthesis of pyocyanin from P. aeruginosa PA14Results: The extracts of Citrus sinensis, Laurus nobilis, Elettaria cardamomum, Allium cepa, and Coriandrum sativum exhibited potent quorum quenching effect. On the other hand, Psidium guajava and Mentha longifolia extracts showed lower QSI activity. These extracts exhibited significant elimination of pyocyanin formation and biofilm development of Pseudomonas aeruginosa PA14. In addition, they significantly inhibited twitching and swimming motilities of P. aeruginosa PA14. Conclusion: This study illustrated for the first time the importance of C. sinensis, L. nobilis, E. cardamomum, A. cepa, and C. sativum as quorum sensing inhibitors and virulence suppressors of P. aeruginosa.